2017
DOI: 10.1111/joop.12179
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of supervisor support: Resolving paradoxical patterns across gender and race

Abstract: This work reconciles previous discrepancies regarding when and how the demographic composition of supervisor–subordinate dyads relates to perceived supervisor support. We draw from social identity theory to argue that building relationships with higher‐status group members, while distancing oneself from the lower‐status group, is a contextually induced way female and racial minority employees may cope with identity threat in the workplace. Our results supported the hypotheses, indicating that this self‐distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 84 publications
(122 reference statements)
3
31
0
Order By: Relevance
“…Across studies, supervisor support had a positive effect on worker well‐being, parenting, and child outcomes, and, for the most part, these findings held up across gender and social class. The very little we could find on race suggests that the context of the workplace, high or low in gender and racial diversity, may moderate the effect of relationships between supervisors and workers (Paustian‐Underdahl, King, Rogelberg, Kulich, & Gentry, ). Important new directions for research on supervisors include examining the “match” between supervisor and supervisee in terms of race and gender as well attending to the the diversity of the broader work context.…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…Across studies, supervisor support had a positive effect on worker well‐being, parenting, and child outcomes, and, for the most part, these findings held up across gender and social class. The very little we could find on race suggests that the context of the workplace, high or low in gender and racial diversity, may moderate the effect of relationships between supervisors and workers (Paustian‐Underdahl, King, Rogelberg, Kulich, & Gentry, ). Important new directions for research on supervisors include examining the “match” between supervisor and supervisee in terms of race and gender as well attending to the the diversity of the broader work context.…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…Lack of ingroup support has also been reported from the perspective of achieved low-status individuals. Research showed that female employees and Non-White employees felt less support from ingroup supervisors (i.e., female and Non-White supervisors) than from outgroup supervisors (i.e., male or White supervisors) in organizations with an adverse diversity climate ( Paustian-Underdahl et al, 2017 ). Such parallel findings across social categories suggest that low ingroup concern among socially mobile women is not specific to gender, and that it can be broadly attributed to the status dynamics between different group memberships.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has examined how experiences of sexism affect managers' attitudes towards their subordinates Derks et al, 2016), and subordinates' attitudes towards their managers (Sterk, Meeussen, & Van Laar, 2018). For instance, Paustian-Underdahl et al (2017) found that women feel less supported by their female supervisors than by their male supervisors. Here, we show that managers' attitudes might similarly impact relationships among their subordinates.…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…The particular focus of this article is on organisational tolerance of sexism, which therefore refers to the absences of practices, procedures, and norms about the inappropriateness of sexism in the workplace. Importantly, organisational climates can also be expressed at the interpersonal level (Paustian-Underdahl, King, Rogelberg, Kulich, & Gentry, 2017), for instance by managers and by peers (Madlock & Booth-Butterfield, 2011), and having a high-level organisational policy that clarifies intolerance of discrimination does not mean that this necessarily translates into similar levels of intolerance of discrimination at lower levels in the organisation (Brady, Kaiser, Major, & Kirby, 2015;Hebl, Foster, Mannix, & Dovidio, 2002). In this article, then, organisational climate is operationalised at three levels, namely the extent to which (a) peers, (b) managers, and (3) organisational policies do or do not reject sexism and support those targeted by sexist treatment.…”
Section: The Role Of Organisational Climatementioning
confidence: 99%